Paracetamol (acetaminophen) for patent ductus arteriosus in preterm or low birth weight infants - Ohlsson, Arne (Cochrane Database Syst Rev, 2018)
BACKGROUND: In preterm newborns, the ductus arteriosus frequently fails to close and the infants require medical or surgical closure of the patent ductus arteriosus (PDA). A PDA can be treated surgically; or medically with one of two prostaglandin inhibitors, indomethacin or ibuprofen. Case reports suggest that paracetamol may be an alternative for the closure of a PDA. An association between prenatal or postnatal exposure to paracetamol and later development of autism or autism spectrum disorder has been reported. OBJECTIVES: To determine the effectiveness and safety of intravenous or oral paracetamol compared with placebo or no intervention, intravenous indomethacin, intravenous or oral ibuprofen, or with other cyclo‐oxygenase inhibitors for treatment of an echocardiographically diagnosed PDA in preterm or low birth weight infants. SEARCH METHODS: We used the standard search strategy of Cochrane Neonatal to search the Cochrane Central Register of Controlled Trials (CENTRAL 2017, Issue 10), MEDLINE via PubMed (1966 to 6 November 2017), Embase (1980 to 6 November 2017), and CINAHL (1982 to 6 November 2017). We searched clinical trial databases, conference proceedings, and the reference lists of retrieved articles for randomised controlled trials (RCT) and quasi‐randomised trials. SELECTION CRITERIA: We included RCTs in which paracetamol was compared to no intervention, placebo or other agents used for closure of PDA irrespective of dose, duration and mode of administration in preterm (≤ 34 weeks' postmenstrual age) infants. We both reviewed the search results and made a final selection of potentially eligible articles by discussion. We included studies of both prophylactic and therapeutic use of paracetamol. DATA COLLECTION AND ANALYSIS: We performed data collection and analyses in accordance with the methods of the Cochrane Neonatal Review Group. We used the GRADE approach to assess the quality of evidence for the following outcomes when data were available: failure of ductal closure after the first course of treatment; neurodevelopmental impairment; all‐cause mortality during initial hospital stay (death); gastrointestinal bleed or stools positive for occult blood; and serum levels of creatinine after treatment (µmol/L). MAIN RESULTS: We included eight studies that reported on 916 infants. One of these studies compared paracetamol to both ibuprofen and indomethacin. Five studies compared treatment of PDA with paracetamol versus ibuprofen and enrolled 559 infants. There was no significant difference between paracetamol and ibuprofen for failure of ductal closure after the first course of drug administration (typical risk ratio (RR) 0.95, 95% confidence interval (CI) 0.75 to 1.21; typical risk difference (RD) −0.02, 95% CI −0.09 to 0.09); I² = 0% for RR and RD; moderate quality of evidence. Four studies (n = 537) reported on gastrointestinal bleed which was lower in the paracetamol group versus the ibuprofen group (typical RR 0.28, 95% CI 0.12 to 0.69; typical RD −0.06, 95% CI −0.09 to −0.02); I² = 0% for RR and RD; number needed to treat for an additional beneficial outcome (NNTB) 17 (95% CI 11 to 50); moderate quality of evidence. The serum levels of creatinine were lower in the paracetamol group compared with the ibuprofen group in four studies (moderate quality of evidence), as were serum bilirubin levels following treatment in two studies (n = 290). Platelet counts and daily urine output were higher in the paracetamol group compared with the ibuprofen group. One study reported on long‐term follow‐up to 18 to 24 months of age following treatment with paracetamol versus ibuprofen. There were no significant differences in the neurological outcomes at 18 to 24 months (n = 61); (low quality of evidence). Two studies compared prophylactic administration of paracetamol for a PDA with placebo or no intervention in 80 infants. Paracetamol resulted in a lower rate of failure of ductal closure after 4 to 5 days of treatment compared to placebo or no intervention which was of borderline significance for typical RR 0.49 (95% CI 0.24 to 1.00; P = 0.05); but significant for typical RD −0.21 (95% CI −0.41 to −0.02); I² = 0 % for RR and RD; NNTB 5 (95% CI 2 to 50); (low quality of evidence). Two studies (n = 277) compared paracetamol with indomethacin. There was no significant difference in the failure to close a PDA (typical RR 0.96, 95% CI 0.55 to 1.65; I² = 11%; typical RD −0.01, 95% CI −0.09 to 0.08; I² = 17%) (low quality of evidence). Serum creatinine levels were significantly lower in the paracetamol group compared with the indomethacin group and platelet counts and daily urine output were significantly higher in the paracetamol group. AUTHORS' CONCLUSIONS: Moderate‐quality evidence according to GRADE suggests that paracetamol is as effective as ibuprofen; low‐quality evidence suggests paracetamol to be more effective than placebo or no intervention; and low‐quality evidence suggests paracetamol as effective as indomethacin in closing a PDA. There was no difference in neurodevelopmental outcome in children exposed to paracetamol compared to ibuprofen; however the quality of evidence is low and comes from only one study. In view of concerns raised regarding neurodevelopmental outcomes following prenatal and postnatal exposure to paracetamol, long‐term follow‐up to at least 18 to 24 months' postnatal age must be incorporated in any studies of paracetamol in the newborn population. At least 19 ongoing trials have been registered. Such trials are required before any recommendations for the possible routine use of paracetamol in the newborn population can be made.